Respuesta :

Answer:

  1

Step-by-step explanation:

The quadratic relation is a perfect square:

  y = (7x +3)²

so has one zero, where the factor is zero:

  7x +3 = 0

  7x = -3

  x = -3/7

_____

It is useful to have handy reference to the form of the square of a binomial:

  (a +b)² = a² +2ab +b²

Here, your first clue is that 49x² and 9 are both perfect squares: (7x)² and (3)². It is easy to check that the middle term is twice the product of these roots:

  2(7x)(3) = 42x . . . . matches the middle term

So, the given expression is equivalent to ...

  y = (7x +3)²

Ver imagen sqdancefan